Relationship between carotid atherosclerosis and lipoprotein (a) in patients with acute ischemic stroke - Zhao, Yongna; Wang, Zhichao; Ji, Ruijun; Wang, Yongjun; Zhang, Yaguang; Yu, Kai (Frontiers in Neurology, 2024)
Objective: This study aimed to examine the relationship between lipoprotein (a) (Lp[a]) and other blood lipid indexes and carotid artery atherosclerosis in patients with acute ischemic stroke (AIS). Methods: A total of 2,018 patients were selected from the hospital ‘acute stroke intervention and secondary prevention registration database’ by identifying blood fat indexes (cholesterol, triglyceride, high-density lipoprotein cholesterol, low-density lipoprotein cholesterol and Lp[a]). Based on the results of carotid artery ultrasound examinations, the patients were divided into a ‘no plaque’ group, comprising 400 patients, a ‘plaque and no stenosis’ group, comprising 1,122 patients and a ‘carotid stenosis’ group, comprising 496 patients. The relationship between Lp(a) and blood lipid indexes and carotid artery atherosclerosis was then investigated using multi-factor logistics regression analysis. Results: There were 400 patients (19.8%) with no carotid plaque, 1,122 patients (55.6%) with plaque and no carotid stenosis and 496 patients (24.6%) with carotid stenosis. As the degree of carotid artery atherosclerosis increased, the Lp(a) level gradually increased; Lp(a) and cholesterol were identified as independent risk factors for carotid atherosclerosis. Conclusion: Lipoprotein (a) and cholesterol are independent risk factors for patients with AIS with carotid atherosclerosis, and their levels increase with the degree of carotid artery atherosclerosis; therefore, attention should focus on levels of cholesterol and Lp(a) in acute stroke patients to control atherosclerosis effectively.